Democratic regression in Indonesia: Police and low-capacity democracy in Jokowi's administration (2014–2020) - Sarah Nuraini Siregar; Riaty Raffiudin; Firman Noor (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2022)
Discussions about democratisation have often revolved around the strengthening or weakening phenomenon/notion of democracy. This research is a continuation of previous studies on democratic regression in Indonesia. Charles Tilly (2007) examined democratic regression from democracy and de-democratization theory through the concept of low-capacity democracy. Tilly's perspective argues a low-capacity democratic process occurred during the Joko Widodo administration in Indonesia from 2014 to 2020 when the state implemented the Police as a political instrument to maintain power. As a result, the character of the Police deviated from democratic principles, leading to a problem for police professionalism. The study employs qualitative methods, in which the primary data is obtained from in-depth interviews with several key informants. The secondary data is gathered from scientific works of literature and news in online media. This study indicates how low-capacity democracy developed through: first, the Indonesian regime's intervention and exercise of control by involving and appointing police officers to civilian positions; second, police repression against civil liberties; and third, the Police's justification for their authority and power. Thus, this study confirms Tilly's argument that a low-capacity democratic process occurs when democratic countries pursue undemocratic methods by manipulating the Police as an instrument to strengthen the power of the regime. The recommendation of this study is to strengthen democracy in terms of law enforcement by the supervision of parliament and supervisory institutions to retain the Police’s role as an independent law enforcement institution.